Bioabsorbable ureteral stents: current state-of-the-art - A. A. Aloyan; I. A. Gorgotsky; N. S. Korbina; V. P. Britov; I. V. Semenyakin; D. D. Shkarupa; N. K. Gadzhiev (Вестник урологии)
Ureteral stenting is one of the main methods for draining the upper urinary tract. The main drawbacks associated with the use of ureteral stents include high treatment costs, stent-associated symptoms, "forgotten" ureteral stents, encrustation, and polymer recycling after stent removal. Biodegradable ureteral stents may be solution for mentioned problems, oﬀering several advantages: (1) avoidance of stent removal, reducing invasion procedures and health costs; (2) prevention of "forgotten" stents; (3) improvement of quality of life; (4) reduction in carbon footprint. This article presents a literature review of the recent developments in biodegradable stent technology.